2011
DOI: 10.1167/iovs.11-7611
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ON-Bipolar Cell Responses of Cone Electroretinograms in Rabbits with the Pro347Leu Rhodopsin Mutation

Abstract: A depolarizing pattern of the cone ERG responses was seen in Pro347Leu Tg rabbits. The enhancement or preservation of the ON-bipolar cell response in the ERGs contributed to shaping the waveform in the Tg rabbits. In this model, the functional alterations in the ON-pathway took place before the deterioration of cone photoreceptor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Similarly, detailed ERG studies in rhodopsin P347L Tg pigs and rabbits have demonstrated that the electrical activities of the cone ON-pathway were also enhanced at a relatively early stage of retinal degeneration. 18,23 In addition, an increase in the ERG responses from the inner retina (e.g., scotopic threshold response) was also reported in the retina of the aged Royal College of Surgeons rat, a rodent model of retinal degeneration. 24,25 Taken together, inherited retinal diseases associated with progressive photoreceptor degeneration may lead to different types of functional changes in the post-photoreceptoral retinal circuits, including the ON-and OFF pathways, during a relatively early stage of retinal degeneration.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, detailed ERG studies in rhodopsin P347L Tg pigs and rabbits have demonstrated that the electrical activities of the cone ON-pathway were also enhanced at a relatively early stage of retinal degeneration. 18,23 In addition, an increase in the ERG responses from the inner retina (e.g., scotopic threshold response) was also reported in the retina of the aged Royal College of Surgeons rat, a rodent model of retinal degeneration. 24,25 Taken together, inherited retinal diseases associated with progressive photoreceptor degeneration may lead to different types of functional changes in the post-photoreceptoral retinal circuits, including the ON-and OFF pathways, during a relatively early stage of retinal degeneration.…”
Section: Discussionmentioning
confidence: 84%
“…15,16,18 The drugs were dissolved in sterile PBS, and the pH was titrated to 7.4 with hydrochloric acid or sodium hydrate. The drugs were injected into the vitreous with a 30-gauge needle inserted through the pars plana approximately 1 mm posterior to the limbus.…”
Section: Drug Injectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, several ERG studies using pharmacologic dissection of the retinal circuits in this model revealed an Copyright 2017 The Authors iovs.arvojournals.org j ISSN: 1552-5783 enhancement of the function of the second-or third-order retinal neurons. [16][17][18] This rabbit model of RP has at least two benefits in ERG analyses compared with the rodent models of eyes with RP. The first is that rabbits have large eyes, which allowed us to perform multiple intravitreal injections of different agents.…”
mentioning
confidence: 99%